Complication Rates in Early Versus Late Cranioplasty—A 14-Year Single-Center Case Series. (18th November 2021) - Tora, Muhibullah S; Malcolm, James G; Mahmooth, Zayan; Pujari, Amit; Rindler, Rima S; Boulis, Nicholas M; Pradilla, Gustavo; Grossberg, Jonathan A; Ahmad, Faiz U
Graphical Abstract: